Effect of different turbulence models on combustion chamber pressure using computational fluid dynamic (CFD) - Mohd Nasruddin, Amir Nazri (2009)
This thesis deals with the numerical study about the effect of different turbulent models on combustion chamber pressure during the event compression and combustion process using Computational Fluid Dynamic (CFD). The assessment is based on cylinder pressure and computational time predicted by the turbulence models. The vital point for the study is the on effect of different turbulence models on simulating the critical process of combustion in cylinder. The most accurate and time efficient models is k-ω-sst. The predicted results produce 58.2358 % discrepancy in term of cylinder pressure. The model also predicted the shortest convergence time which is 1573 minute. The selection of the models must be right in using numerical modelling approach in order to fulfil three major criteria which are accuracy, computational time and cost. This study consists of numerical modelling by using Mitsubishi magma 4G15 as baseline engine design. Engine speed at 2000 rpm was selected as baseline for initial condition. This project simulates the compression and combustion process right after intake valve closed until exhaust opened. For numerical modelling approach, there were six turbulence models selected which are k-ϵ-standard, k-ϵ-RNG, k-ϵ-realizable, k-ωstandard, k-ω-SST, and RSM-Linear Pressure Strain. The pressure data for turbulent models validate by compared to the experimental data. However, there are discrepancies of the results due to improper boundary condition and inherit limitation of model. For further simulation of combustion process must consider detail mixture properties, detail boundary condition and model extension for better accuracy.